Assessing the Hydrology of a Data-Scarce Tropical Watershed Using the Soil and Water Assessment Tool - Winfred, B. M.; Japhet, J. K. (Scientific Research Publishing, Inc., 2017)
The hydrology of the Little Ruaha River which is a major catchment of the Ihemi Cluster in the Southern Agricultural Growth Corridor of Tanzania (SA-GCOT) has been studied. The study focused on the hydrological assessment through analysis of the available data and developing a model that could be used for assessing impacts of environmental change. Pressures on land and water resources in the watershed are increasing mainly as a result of human activities, and understanding the hydrological regime is deemed necessary. In this study, modeling was conducted using the Soil and Water Assessment Tool (SWAT) in which meteorological and streamflow data were used in the simulation, calibration and evaluation. Calibration and evaluation was done at three gauging stations and the results were deemed plausible with NSE ranging between 0.64 and 0.80 for the two stages. The simulated flows were used for gap filling the missing data and generation of complete daily time series of streamflow at three gauging stations of Makalala, Ihimbu and Mawande. Results of statistical trends and flow duration curves, revealed decline in magnitudes of seasonal and annual flows indicating that streamflows are changing with time and may have implications on envisioned development and the water dependent ecosystems.